Membangun Generasi Berintegritas Pendidikan Karakter dalam Kurikulum Nasional di Sekolah Dasar - Hotmian Situmorang; Indri Anggraini; Cut Kumala Sari (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
With an emphasis on two key values responsibility and creativity this study attempts to evaluate how character education implementation shapes students' integrity at SDN 2 Karang Anyar. Data were gathered through documentation studies, teacher and principal interviews, and observation using a qualitative methodology. "The results of the study indicate that character education has been implemented quite well in class VI C. Students showed a good level of responsibility in completing individual and group assignments, although there were still obstacles such as lack of motivation and consistency. On the other hand, students' creativity developed well, especially in science and mathematics subjects, supported by their closeness to technology and social media. Differences in character between students require a varied and personalized learning approach. The active role of teachers in directing and supervising individual student differences greatly influences the success of character education at SDN 2 Karang Anyar. To maximize student character development, this study suggests the use of a more interactive learning approach and the arrangement of customized learning strategies.